The Administration of Criminal Justice Act, 2015: Pathway to A Reformed Criminal Justice System in Nigeria - Omachi, Mary Jennifer; Sule, Anthony Abakpa (ABUAD Law Journal, 2019)
Since the laws regulating crime touch upon the important areas of social life, legal systems have continued to imbibe best practises to regulate crimes within their jurisdictions in order to encourage development and ensure progress. Thus, a good criminal justice system ensures that effective laws are put in place to fit growing societal demands which are never static. Nigeria, in regulating criminal proceedings, had relied on obsolete laws existing since the colonial and post-colonial eras to 2015 when the Administration of Criminal Justice Act was enacted to fit the growing demands of the Nigerian society. This research uses the doctrinal method to appraise certain innovations of the Act and show how they can reform the criminal justice system in the country to align with best practices around the world. Even though the enactment of the Act is a welcome development, its application is limited only to federal courts (except a court martial) and courts within the Federal Capital Territory, Abuja. Whereas the laudable innovative provisions are highly commendable they can only be effectively applied if they are well implemented. Hence the need for government to effectively fund the criminal justice sector with appropriate manpower, resources and structures and the need for all the states within the country to enact their own Administration of Criminal Justice Laws to apply uniformly in the country.